ID 284 – Abnormal delta cortical sources of resting state eyes closed EEG rhythms correlate with cerebrospinal fluid (CSF) ® amyloid (A®) level in amnesic MCI subjects. Issue 3 (March 2016) - Noce, G.; Del Percio, C.; Marzano, N.; Cordone, S.; Bagnoli, C.; Rossini, P.M.; Soricelli, A.; Nobili, F.M.; Bartres Faz, D.; Blin, O.; Payoux, P.; Bordet, R.; et al.
Abstract : Aim: In the framework of IMI PharmaCog project (Grant Agreement no. 115009), this study evaluated whether abnormal cortical sources of resting state electroencephalographic (EEG) rhythms are correlated to cerebrospinal fluid (CSF) ® amyloid (A®) level in amnesic Mild Cognitive Impairment (MCI) subjects. Methods: Artifact-free resting state eyes-closed EEG rhythms (19 electrodes) were recorded. Individual datasets were divided into those with high CSF A® level (81 A®-negative, CSF A ® > 550 pg / ml ) and those with low CSF A® level (46 A®-positive, CSF A ® < 550 pg / ml ). Regional normalized cortical sources of EEG rhythms at frequency bands of interest were estimated by LORETA package. ANOVA compared these sources between the two MCI groups ( p  < 0.05, corrected) and 50 cognitively normal elderly (Nold) subjects. Results: Statistical results showed: (1) source pattern Nold < A®-negative < A®-positive at frontal, temporal and limbic delta sources level; (2) significant negative correlation (Pearson test, p  < 0.05) between temporal delta sources and CSF A® level ( r  = −0.26; p  = 0.003) across all MCI subjects. Conclusions: These results suggest a relationship between the brain amyloid charge, as revealed by CSF A® level, and pathological delta cortical sources indicating cortical disconnection in amnesic MCI subjects. EEG delta sources could represent a promising early diagnostic marker of Alzheimer's disease (AD).